The Influence of Financial Knowledge, Financial Attitude and Personality on Financial Management Behavior of Contemporary Batik Craft MSMEs - Qur’ani, Ramita Divta; Zulkifli, Zulkifli (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study aims to analyze the influence of financial knowledge, financial attitudes, and This study aims to examine the influence of financial knowledge, financial attitudes, and personality on financial management behavior in contemporary batik craft MSMEs actors in region B. MSMEs have an important role in the local economy, but still face various challenges in effective financial management. This study uses a quantitative approach with a purposive sampling technique on 64 respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that financial knowledge, financial attitudes, and personality each have a positive and significant influence on financial management behavior. The three variables also simultaneously showed a significant influence, with an adjusted R² value of 0.831, which means that this model is able to explain 83.1% of the variation in financial management behavior. These findings emphasize the importance of financial literacy, the formation of a positive attitude towards financial management, and personality traits that support strengthening the financial capabilities of MSMEs actors. This study is expected to be a reference in designing more effective and sustainable MSMEs development training and policies.